NUMERICAL SIMULATION OF EXPLOSIVE VOLCANIC ERUPTIONS FROM THE CONDUIT FLOW TO GLOBAL ATMOSPHERIC SCALES - Textor C.; Graf H.-F.; Timmreck C.; Longo A.; Neri A.; Ongaro T.E.; Papale P.; Ernst G.G.J. (My University, 2005)
Volcanic eruptions are unsteady multiphase phenomena, which encompass many inter-related processes across the whole range of scales from molecular and microscopic to macroscopic, synoptic and global. We provide an overview of recent advances in numerical modelling of volcanic effects, from conduit and eruption column processes to those on the Earth's climate. Conduit flow models examine ascent dynamics and multiphase processes like fragmentation, chemical reactions and mass transfer below the Earth surface. Other models simulate atmospheric dispersal of the erupted gas-particle mixture, focusing on rapid processes occurring in the jet, the lower convective regions, and pyroclastic density currents. The ascending eruption column and intrusive gravity current generated by it, as well as sedimentation and ash dispersal from those flows in the immediate environment of the volcano are examined with modular and generic models. These apply simplifications to the equations describing the system depending on the specific focus of scrutiny. The atmospheric dispersion of volcanic clouds is simulated by ash tracking models. These are inadequate for the first hours of spreading in many cases but focus on long-range prediction of ash location to prevent hazardous aircraft - ash encounters. The climate impact is investigated with global models. All processes and effects of explosive eruptions cannot be simulated by a single model, due to the complexity and hugely contrasting spatial and temporal scales involved. There is now the opportunity to establish a closer integration between different models and to develop the first comprehensive description of explosive eruptions and of their effects on the ground, in the atmosphere, and on the global climate.